2016
DOI: 10.1007/s11999-015-4501-9
|View full text |Cite
|
Sign up to set email alerts
|

Acetabuloplasties at Open Reduction Prevent Acetabular Dysplasia in Intentionally Delayed Developmental Dysplasia of the Hip: A Case-control Study

Abstract: Background Avascular necrosis (AVN) and residual acetabular dysplasia are the two main complications of developmental dysplasia of the hip (DDH) treatment. Although early reduction of the hip may decrease the incidence of residual dysplasia, it may increase the incidence of AVN and vice versa. However, we do not know if changes in surgical technique may lead to a modification in these outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Akagi et al [27] in their study showed that the main factor affecting the acetabular development is open reduction and maintenance of reduction. Performance of incomplete periacetabular osteotomy has been proposed to trigger acetabular remodeling [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Akagi et al [27] in their study showed that the main factor affecting the acetabular development is open reduction and maintenance of reduction. Performance of incomplete periacetabular osteotomy has been proposed to trigger acetabular remodeling [28].…”
Section: Discussionmentioning
confidence: 99%
“…[27] in their study showed that the main factor affecting the acetabular development is open reduction and maintenance of reduction. Performance of incomplete periacetabular osteotomy has been proposed to trigger acetabular remodeling [28]. Osteotomy itself is believed to stimulate periosteal ossification in its surroundings resulting in development of the rim of the acetabulum [5].…”
Section: Discussionmentioning
confidence: 99%
“…Several possible complications might occur after DDH treatment. Clearly, hip stiffness in DDH is unavoidable in the course of surgical treatment that involves open hip reduction and lengthy periods of immobilization, and is considered one of the most common complication [ 12 , 13 ]. However, local muscular spasm of the operatively treated hip has never been reported and that posed a diagnostic dilemma in our case as clinical presentations of stiffness and spasm share several similarities.…”
Section: Discussionmentioning
confidence: 99%
“…After reading the full text of the remaining 61 studies, three reviews and four meta-analysis studies were excluded, 13 studies were excluded because of missing or fuzzy data, 4 studies with duplicate data were excluded, 15 studies with an age of reduction ≥3 years old were excluded, and 8 studies involving only one treatment method were excluded. Finally, 14 articles [15,17,[22][23][24][25][26][27][28][29][30][31][32][33] were included. The literature retrieval process is illustrated in Fig.…”
Section: Study Selectionmentioning
confidence: 99%